Odpowiedź :
3x - 4 = 3/4 x //*4
12x - 16 = 3x
9x = 16 //:9
x = 16/9
3(x-1) = 3x - 1
3x - 3 = 3x - 1
3x - 3x = -1 + 3
0 = 2
sprzeczność
czyli zbiór pusty
-1/4 x = 2,4 //*4
-x = 9,6 //*(-1)
x = -9,6
2 + 0,3x = - 1 1/2x
2 + 3/10x = - 3/2x //*10
20 + 3x = -15x
18x = -20 //:18
x = -18/20 = -10/9
12x - 16 = 3x
9x = 16 //:9
x = 16/9
3(x-1) = 3x - 1
3x - 3 = 3x - 1
3x - 3x = -1 + 3
0 = 2
sprzeczność
czyli zbiór pusty
-1/4 x = 2,4 //*4
-x = 9,6 //*(-1)
x = -9,6
2 + 0,3x = - 1 1/2x
2 + 3/10x = - 3/2x //*10
20 + 3x = -15x
18x = -20 //:18
x = -18/20 = -10/9